2011
DOI: 10.5152/tjh.2011.49
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic leukocytes in cardiac surgery: Good or bad?

Abstract: Worldwide, cardiac surgery is a common procedure requiring a large quantity of allogeneic blood products, which are associated with postoperative complications. Leukocytes present in blood products may play a role in these complications, which are referred to as transfusion-related immunomodulation (TRIM). Several randomized controlled trials (RCTs) in different settings investigated the effects of allogeneic leukocytes in red blood cells (RBCs). Cardiac surgery studies reported a reduction in postoperative in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 69 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…Activated neutrophils secrete a variety of cytokines, including IL-1, IL-6, TNFalpha and PAF, which are associated with sustained airway injury, airway smooth muscle thickening and airway remodeling [17]. Previous studies reported BPI as a key marker of neutrophil activation [18,19]; therefore, we hypothesized that the increase in BPI levels is associated with asthma.…”
Section: Discussionmentioning
confidence: 93%
“…Activated neutrophils secrete a variety of cytokines, including IL-1, IL-6, TNFalpha and PAF, which are associated with sustained airway injury, airway smooth muscle thickening and airway remodeling [17]. Previous studies reported BPI as a key marker of neutrophil activation [18,19]; therefore, we hypothesized that the increase in BPI levels is associated with asthma.…”
Section: Discussionmentioning
confidence: 93%
“…It is quite difficult to remove all confounding factors to evaluate the independent effect of leukoreduction on LOS. 26 This was probably the reason for controversial results in previous studies. [16][17][18]20,22,27 Moreover, these studies were conducted more than a decade ago, so we can presume an overall improvement in the health care system playing a major role in reducing infection.…”
Section: Discussionmentioning
confidence: 99%
“…The LOS of a patient in the ICU or in the hospital depends on various factors like comorbidity of the patient, length of surgery, duration of anaesthesia, use of drugs and postoperative infections. It is quite difficult to remove all confounding factors to evaluate the independent effect of leukoreduction on LOS 26 . This was probably the reason for controversial results in previous studies 16‐18,20,22,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide approximately 1,000,000 patients undergo cardiac surgery annually. [ 13 ] Although several blood conservation strategies are now being employed, allogenic blood transfusions play a crucial role in these advanced surgical procedures. Patients undergoing cardiac surgeries consume a large proportion of RBC units, estimated at approximately 20% of the total blood supply.…”
Section: Discussionmentioning
confidence: 99%